Little Miss Stoneybrook... and Dawn - Martin, Ann M., 1955- (Martin, Ann M., 1955- Baby-sitters Club, 2021)
Dawn's a little jealous when there's a formal ceremony to welcome Jessi and Mallory into the Baby-sitters Club. Don't people know that Dawn's a special baby-sitter too? Then it's Dawn's turn to shine. Mrs. Pike wants Dawn to help prepare Margo and Claire for the Little Miss Stoneybrook contest. So what if Margo's only talent is peeling a banana with her feet? Dawn's going to help her charges win that contest any way she can. The only trouble is...Kristy, Mary Anne, and Claudia are helping Karen, Myriah, and Charlotte enter the contest, too. And nobody's sure where the competition is fiercer: at the pageant -- or at the Baby-sitters Club! The best friends you'll ever have!